The mechanisms of synchronization in strategic alliances - Gofredo, Tânia Regina; Bataglia, Walter (Revista de Administração da UFSM, 2015)
Industries characterized by the distribution of knowledge among its actors have adopted a governance structure based on contractual strategic alliances for a number of organizational activities such as research and development, manufacturing, marketing, distribution and supply. On one hand alliances are fundamental to the performance of these sectors, on the other, there is a 50% rate of failure of these alliances, as its management, demand integration efforts of the activities developed jointly by independent partners is still a major challenge, with impact on coordination costs. Accordingly, with this article, by means of qualitative research and the exploratory case study, we sought to show the importance that the mechanisms of synchronization and its main microfoundations − individuals, processes and estructures − the relational capacity, carry on the good management of contractual strategic alliances.